An Overview of Commercially Available Apps in the Initial Months of the COVID-19 Pandemic - Zhang, Melvyn W. B.; Chow, Aloysius; Ho, Roger C. M.; Smith, Helen E. (Frontiers in Psychiatry, 2021)
Introduction It has been four months since the discovery of COVID-19, and there have been many measures introduced to curb movements of individuals to stem the spread. There has been an increase in the utilization of web-based technologies for counselling, and for supervision and training, and this has been carefully described in China. Several telehealth initiatives have been highlighted for Australian residents. Smartphone applications have previously been shown to be helpful in times of a crisis. Whilst there have been some examples of how web-based technologies have been used to support individuals who are concerned about or living with COVID-19, we know of no studies or review that have specifically looked at how M-Health technologies have been utilized for COVID-19. Objectives There might be existing commercially available applications on the commercial stores, or in the published literature. There remains a lack of understanding of the resources that are available, the functionality of these applications, and the evidence base of these applications. Given this, the objective of this content analytical review is in identifying the commercial applications that are available currently for COVID-19, and in exploring their functionalities. Methods A mobile application search application was used. The search terminologies used were “COVID” and “COVID-19”. Keyword search was performed based on the titles of the commercial applications. The search through the database was conducted from the 27th March through to the 18th of April 2020 by two independent authors. Results A total of 103 applications were identified from the Apple iTunes and Google Play store respectively; 32 were available on both Apple and Google Play stores. The majority appeared on the commercial stores between March to April 2020, more than 2 months after the first discovery of COVID-19. Some of the common functionalities include the provision of news and information, contact tracking and self-assessment or diagnosis. Conclusions This is perhaps the first review that has characterized the smartphone applications which are currently available, four months after the first discovery of COVID-19.